The Analysis of Use of Paytren Payment System in Increasing Consumer Behavioral Intention - Idris Saleh; Fahrina Mustafa; Mohamad Trio Febriyantoro; Imman Yusuf Sitinjak; Amat Suroso (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
The purpose of this study was to analyze the effect of Perceived Usefulness on Behavioral Intention, to analyze the effect of Perceived Ease of Use on Behavioral Intention and to analyze the effect of Perceived Usefulness and Perceived Ease of Use together on Behavioral Intention. The scope of this study focuses on perceived usefulness, perceived ease of use, as independent variables, and behavioral intention as the dependent variable. Henceforth, these variables will be analyzed to what extent these variables affect the process stage of consumer behavioral intention (the dependent variable) in PayTren application users. This research was conducted on 100 Paytren application users in the Greater Jakarta area. This research was conducted by providing questionnaires in the form of online questionnaires using Google Doc media and data collection was carried out over a period of two months from March to May 2022. Based on the research that has been done and the results obtained, the conclusions that can be drawn in research regarding the analysis of the use of the PayTren payment system in fostering consumer behavioral intention, it can be concluded as follows, the variable perceived usefulness has a partially significant effect on behavioral intention. The perceived ease of use variable has a partially significant effect on behavioral intention. The variable perceived usefulness, perceived ease of use simultaneously has a significant influence simultaneously on behavioral intention.